2011
DOI: 10.1002/hed.21962
|View full text |Cite
|
Sign up to set email alerts
|

UM‐SCC‐104: A New human papillomavirus‐16–positive cancer stem cell–containing head and neck squamous cell carcinoma cell line

Abstract: BACKGROUND Few human papillomavirus (HPV)-positive head and neck squamous cell carcinoma (HNSCC) cell lines exist. We established UM-SCC-104, a new HPV(+) HNSCC cell linefrom a recurrent oral cavity tumor, and characterized it for the presence of cancer stem cells (CSC). METHODS Tumor cells were tested for biomarker expression by immunohistology and the presence of HPV was assessed by several methods. RESULTS UM-SCC-104 has a unique genotype, contains HPV-16 and expresses E6/E7. Inoculation of (Aldehyde De… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
100
0

Year Published

2012
2012
2015
2015

Publication Types

Select...
7
1

Relationship

5
3

Authors

Journals

citations
Cited by 86 publications
(104 citation statements)
references
References 62 publications
4
100
0
Order By: Relevance
“…UM-SCC-47 (Lansford et al 1999) and UM-SCC-104 (Tang et al 2012) were kindly provided by Thomas Carey, University of Michigan; UPCI:SCC090 (White et al 2007) were from Susanne M. Gollin, University of Pittsburgh; UD-SCC-2 (Ballo et al 1999) were from Henning Bier, University of Dusseldorf; and HMS001 cells were from James Rocco, Harvard Medical School. Please see Table 1 and Supplemental Table 1. CAL 27, D562, SCC-25, SiHa, and CaSki cells were cultured as recommended by ATCC.…”
Section: Methods Human Cancer Cell Lines and Primary Tumorsmentioning
confidence: 99%
“…UM-SCC-47 (Lansford et al 1999) and UM-SCC-104 (Tang et al 2012) were kindly provided by Thomas Carey, University of Michigan; UPCI:SCC090 (White et al 2007) were from Susanne M. Gollin, University of Pittsburgh; UD-SCC-2 (Ballo et al 1999) were from Henning Bier, University of Dusseldorf; and HMS001 cells were from James Rocco, Harvard Medical School. Please see Table 1 and Supplemental Table 1. CAL 27, D562, SCC-25, SiHa, and CaSki cells were cultured as recommended by ATCC.…”
Section: Methods Human Cancer Cell Lines and Primary Tumorsmentioning
confidence: 99%
“…To date, the major hurdle for HPV/OPSCC screening is the paucity of relevant HPV/ OPSCC cell line models to be used for larger scale drug screening. Currently, there are only 5 HPV/HNC cell lines reported (UD-SCC-2 from hypopharynx, UPCI:SCC90 from the base of tongue, UM-SCC47 from lateral tongue, 93-VU-147T from the floor of the mouth and UM-SCC-104 from recurrent oral cavity [20]; and only one of these was derived from the oropharynx (UPCI:SCC90). Therefore, the development of additional HPV/OPSCC cell models will be of paramount importance to enhance the drug development process for HPV/OPSCC.…”
Section: Lack Of Preclinical Therapeutic Studies In Hpv/ Opscc Modelsmentioning
confidence: 99%
“…Some studies have observed high expression of nuclear p53 in some human papillomavirus-containing tumors with wild-type p53 (Hafkamp et al, 2003), and other studies demonstrating low p53 expression (Wilczynski et al, 1998). Mechanism of overexpression of wild-type p53 in the presence of the virus is known (Tang et al, 2011).…”
Section: P16 Expressingmentioning
confidence: 99%
“…The variability of high risk human papillomavirus containing cell lines enhances our ability to study the role that human papillomavirus plays in head and neck squamous cell carcinoma development and response or resistance to therapy (Tang et al, 2011). Combination of several risk factors could explain this.…”
Section: P16 Expressingmentioning
confidence: 99%
See 1 more Smart Citation